The wood in the Italian sacred art (and hints of Western Europe) - Nicola Macchioni (Acta Biológica Catarinense, 2025)
MESA-REDONDA 2: MADEIRAS NA ARTE SACRA: ÁRVORES, SIMBOLISMO, CONSERVAÇÃO E RESTAURO